Improved maternal bonding with the use of 3D-printed models in the setting of a facial cleft. Issue 3 (14th August 2018) - Coté, John J; Thomas, Brittany; Marvin, Joseph
Aim: Case presentation of the effects of 3D-printed models on the maternal bonding of two fetuses with facial clefts.Method: In one case the Maternal Antenatal Attachment Scale was used to score maternal bonding before and after viewing of 3D-printed images. In the other case, the effect of the 3D-printed image was witnessed anecdotally. Both 3D prints were created using polylactic acid on an Ultramaker 2+ printer.Result: In both cases maternal bonding appeared to be improved. Increased global bonding and quality of attachment was quantifiably measured in the second case.Conclusion: 3D-printed models can be a useful addition to patient education and can positively impact maternal–fetal bonding. Further study is required to evaluate how 3D printing can affect maternal bonding in a larger setting.